Efek Antidiare Infusa Daun Senggani (Melastoma malabathricum L.) Pada Mencit Jantan Galur Swiss Webster Yang Di Induksi Oleum ricini - Nova Suliska; Thito Dwi E; Herlinda Herlinda (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Diarrhea is a disorder of defecation more than 3 times a day with the consistency of liquid stool, blood and/or mucus. The plants that is used by the community for diarrhea is senggani (Melastoma malabathricum L.). This study aims to determine the antidiarrheal effects and dose of senggani leaves infusion in mice induced by Oleum ricini. Mice were grouped into 5 groups: the positive control group (diarrhea induction), the comparison group (loperamide), and senggani leaves infusion test group with a dose of 26 mg/kg bw, 52 mg/kg bw, and 104 mg/kg bw. Mice induced diarrhea with Oleum ricini, 30 minutes later the mice were given the samples, except the positive control group. The faecal frequency, weight, and consistency were measured every 30 minutes for 4 hours. Senggani leaves infusion group 52 mg/kg bw showed the frequency and faecal weight were significantly different compared to the positive control group (P <0.5) at 240 minutes observation. The faecal consistency of senggani leaves infusion groups 52 mg/kg bw tends to be normal at 240 minutes observation. Senggani leaves infusion 52 mg/kg bw showed the best antidiarrheal effect compared to senggani leaf infusion 26 mg/kg bw and 104 mg/kg bw in Oleum ricini-induced mice.